Inverted virtual classroom in the learning paradigm - Mejia-Mejia, Elias; Díaz-Flores, Francis (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This paper sustains the thesis that the central problem of pedagogy, and of education in general, is the student’s learning and not, as is commonly asserted, the professor’s teaching or, that they are integrated processes: teaching-learning. The 2020 pandemic has forced to conduct graduate studies virtually, which has shown that, in the asynchronous phase of the process, students perform learning, so we have formulated the following hypothesis: The groups of graduate students who studied virtually, improve their learning levels compared to groups of graduate students who studied face-to-face. To test this hypothesis we have worked with two independent samples. The first one constituted by 300 graduate students who took face-to-face studies in the academic semesters 2019-I and 2019-II, whose final average was 16,3033, and the second one, constituted by 300 graduate students who took virtual studies in the academic semesters 2020-I and 2020-II and whose final average was 17,7533. The Student’s t-test shows that the group of students who took virtual studies significantly improved their learning levels, since the P-value found is 0,000, less than α chosen: 0,05, a result that leads to rejecting the null hypothesis and maintaining the working hypothesis in force.